Clinical Management of Medications in Pregnancy and Lactation. Issue 2 (June 2017) - Temming, L.A.; Cahill, A.G.; Riley, L.E.
Abstract : ( Am J Obstet Gynecol . 2016;214(6):698–702) Studies have shown that use of prescription and over-the-counter medications during pregnancy and lactation is quite high. A clinical case was presented regarding a patient with long-standing depression who was taking a selective serotonin reuptake inhibitor (SSRI) and discovered she was now pregnant. The question was posed as to whether she should continue the drug.